1999
DOI: 10.1073/pnas.96.8.4449
|View full text |Cite
|
Sign up to set email alerts
|

Mice that lack the angiogenesis inhibitor, thrombospondin 2, mount an altered foreign body reaction characterized by increased vascularity

Abstract: Disruption of the thrombospondin 2 gene (Thbs2) in mice results in a complex phenotype characterized chief ly by abnormalities in fibroblasts, connective tissues, and blood vessels. Consideration of this phenotype suggested to us that the foreign body reaction (FBR) might be altered in thrombospondin 2 (TSP2)-null mice. To investigate the participation of TSP2 in the FBR, polydimethylsiloxane (PDMS) and oxidized PDMS (ox-PDMS) disks were implanted in TSP2-null and control mice. Growth of TSP2-null and control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
101
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 145 publications
(108 citation statements)
references
References 32 publications
3
101
0
1
Order By: Relevance
“…Histological analysis of skin showed that collagen fibers are disorganized and lack the normal predominant parallel orientation to the epidermal surface, and examination of these fibers at the electron microscopic level revealed the presence of abnormally large collagen fibrils with irregular contours in tissues from mutant animals. Although the presence of TSP2 as a constituent of collagen fibers could not be documented in the developing or adult mouse (Kyriakides et al, 1998b), TSP2 was found to colocalize with collagen fibers in the tissue responses to injury that accompanied the foreign body reaction (Kyriakides et al, 1999a) and wound healing (Kyriakides et al, 1999b).…”
Section: Introductionmentioning
confidence: 87%
“…Histological analysis of skin showed that collagen fibers are disorganized and lack the normal predominant parallel orientation to the epidermal surface, and examination of these fibers at the electron microscopic level revealed the presence of abnormally large collagen fibrils with irregular contours in tissues from mutant animals. Although the presence of TSP2 as a constituent of collagen fibers could not be documented in the developing or adult mouse (Kyriakides et al, 1998b), TSP2 was found to colocalize with collagen fibers in the tissue responses to injury that accompanied the foreign body reaction (Kyriakides et al, 1999a) and wound healing (Kyriakides et al, 1999b).…”
Section: Introductionmentioning
confidence: 87%
“…Plateletderived growth factor is an FDA-approved therapeutic for wound healing [10]. A study using knockout mice identified thrombospondin2 (TSP2) as a key regulator of the FBR [11]. By delivering antisense cDNA to block the production of TSP2, enhanced angiogenesis and a diffuse collagen deposition (in contrast to dense, highly aligned collagen in the expected capsule) were noted [12].…”
Section: The Future Of Biocompatibilitymentioning
confidence: 99%
“…Further, ultrastructural studies demonstrated that TSP2 influences ECM assembly (15, 16). TSP2 KO mice displayed improved recovery of blood flow following ischemia (17), altered foreign body response (18,19), and accelerated wound healing (16,20,21). In contrast, TSP1 KO mice displayed delayed healing because of insufficient stimulation of inflammation (13).…”
mentioning
confidence: 99%